Ammonia optical gas sensing based on graphene-covered silicon microring resonators: A design space exploration. (May 2021) - Jia, Wei; Majumder, Apratim; Banerji, Sourangsu; Menon, Rajesh; Sensale-Rodriguez, Berardi
Abstract: This paper discusses the design space exploration for an ammonia optical gas sensor based on a silicon microring resonator that is covered by graphene. A comparative analysis of the transmittance sensitivity of its fundamental quasi-TE and quasi-TM modes is presented. Results show that a large fraction of the fundamental quasi-TM mode's electrical energy is propagating outside the waveguide, which makes this geometry more sensitive to ammonia induced changes in Fermi energy of graphene. The overall transmittance intensity difference, for the fundamental quasi-TE mode is less than 1 ​dB, independent of ring radius, when the ammonia gas concentration is varied from 0.5 to 1000 ​ppm. For the fundamental quasi-TM mode, results show that a ring radius ~8.4 ​μm can provide critical coupling condition and lead to >20 ​dB modulation of transmittance intensity when the ammonia gas concentration is varied from 0.5 to 1000 ​ppm. Overall, proper selection of mode excitation as well as ring geometry is essential to attain practical sensitivity.